Pituitary autoantibodies in autoimmune polyendocrinopathy – candidiasis - ectodermal dystrophy (APECED) - O’Dwyer, Damien T.; McElduff, Patrick; Peterson, Pärt; Perheentupa, Jaakko; Crock, Patricia A. (Acta Biomedica Atenei Parmensis, 2007)
Autoimmune polyendocrinopathy - candidiasis - ectodermal dystrophy (APECED) is an autosomal recessive disease due to mutations in the AIRE (AutoImmune REgulator) gene. The role of pituitary autoimmunity in APECED is not known.We determined the prevalence of pituitary autoantibodies in a cohort of 67 Finnish patients with APECED from 217 serum samples collected over 26 years by one investigator. Overall, autoantibodies to the 49 kDa cytosolic autoantigen, human pituitary enolase were detected in 39 of the 67 patients (58%). On their first sample, 25 patients had autoantibodies compared to 5 of 68 controls (chi-square, 1df=17.11, p< 0.001; OR=7.32), but subsequently 14 patients seroconverted between 10 and 53 years of age. Once seropositive, all but two of the patients maintained their positive autoantibody status, even over many years. In the current study all but 7 of the 19 patients known to have high titre anti-candidal enolase antibodies had developed autoantibodies directed against human pituitary enolase. Other pituitary autoantibody reactivities were detected against cytosolic proteins of molecular weights 40-, 45-, 60- and 105 kDa in 15%, 16%, 12% and 3% of patients respectively. Autoantibodies to pituitary enolase are markers of neuroendocrine autoimmunity but seem not to be associated with clinical hypopituitarism in APECED patients.